Efectos derivados de la acción voluntaria: inventario de consecuencias de la acción voluntaria (ICAV) - Fernández, Belén; Yélamos, Carmen; Olivares, Mª Eugenia (Psicooncología, 2004)
The relationship between volunteers and the individuals who benefit from their action focuses on the latters’ problems, and solutions are not always forthcoming. As a result, volunteers who carry out socio-sanitary activities may comprise a high-risk group for burnout syndrome. This effect produces a high incidence in volunteer drop-out, although the level is lower than the one that professionals may sustain. In addition, burnout questionnaires are not sufficiently susceptible for use in volunteer samples. Hence, the need to design sensitive, valid, and reliable instruments, such as the one proposed in this study. The first goal was to verify the psychometric properties of the instrument before drawing any conclusions about the results derived from its use. The psychometric criteria are acceptable, as reliability showed a value of .83, and the criterion validity, using a multiple linear regression model, obtained a regression coefficient of .29 with F= 3.07, and a significance level lower than 0.05. The instrument yielded a factor structure with three orthogonal factors (depression, concern about health, and self-realization). Thus, the ICAVcan be considered a satisfactory instrument to evaluate burnout indicators in a collective –the volunteers–where measuring instruments are lacking, and which is especially relevant in the assistential framework. The second goal was to assess burnout levels with the questionnaire in a sample of 310 volunteers from the Spanish Cancer Association. The results obtained reveal no remarkable alterations derived from the helping relationship. However, a small group of subjects present: affective distancing, impatience, irritability, and feelings of frustration. Similarly, another group of volunteers showed worry, fear, and beliefs of suffering from a severe illness. Hence, the need to compliment volunteers’ training with an adequate selection process, follow-up, and psychological support, if necessary.